Relationship between the severity of agitation and quality of life in residents with dementia living in German nursing homes - a secondary data analysis - Schmüdderich, Kathrin; Holle, Daniela; Stroebel, Armin; Holle, Bernhard; Palm, Rebecca (BMC Psychiatry, 2021)
Background: Severe agitation and its relation to single dimensions of quality of life are not well understood. The aim of this study was to gain more knowledge about severe agitation and to examine the relationships between the severity of agitation and single dimensions of quality of life among residents with dementia living in German nursing homes. Methods: This exploratory secondary analysis included data from 1947 residents of 66 German nursing homes from the DemenzMonitor study. The construct of agitation was defined as a composite score of the items agitation/aggression, irritability/lability and disinhibition from the Neuropsychiatric Inventory Questionnaire (NPI-Q); the resident was classified as severely agitated if at least one of these symptoms was rated as ‘severe’. The single dimensions of quality of life were measured with the short version of the QUALIDEM instrument. To avoid selection bias, two controls with mild or no agitation were selected for each resident with severe agitation using propensity score matching. Mixed linear regression models were then generated to determine the differences in the dimensions of quality of life for the severity of agitation and the defining items. Results: For four out of five dimensions of quality of life of the short version of QUALIDEM, residents with severe agitation had significantly lower values than residents without severe agitation. Converted to scale size, the greatest difference between both groups was found in the dimension social isolation with 23.0% (-2.07 (95% CI: -2.57, -1.57)). Further differences were found in the dimensions restless tense behaviour with 16.9% (-1.52 (95% CI: -2.04, -1.00)), positive affect with 14.0% (-1.68 (95% CI: -2.28, -1.09)) and social relations with 12.4% (-1.12 (95% CI: -1.54, -0.71)). Conclusions: Severe agitation is a relevant phenomenon among nursing home residents with dementia and is associated with lower values of quality of life in the dimensions social isolation, restless tense behaviour, positive affect and social relations from the QUALIDEM instrument. Therefore, more attention should be paid to severe agitation in nursing practice and research. Moreover, care strategies used to reduce severe agitation should be considered in terms of their impact on the dimensions of quality of life.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Aggression; Agitation; Dementia; Nursing home; Quality of life